Rambots: robust robotic systems for outreach - Serff, Everett, author; Fatehiboroujeni, Soheil, advisor; Bailey, Ryan, committee member (Colorado State University. Libraries, 2026)
The use of robotics in outreach and education has been shown to play an important role in motivating student interest in STEM, particularly when interactive experiences and mentorship are involved. Building on this foundation, the Rambot project is a multi-year, multidisciplinary effort focused on developing an accessible quadrupedal robot platform known as Sparky, which the team brings to K-12 STEM outreach events. This year’s project focuses on improving the robot’s functionality and outreach impact through the addition of new capabilities and forward-looking design work. Specifically, the team developed a manipulator arm capable of picking up objects and began early-stage design of a next-generation Rambot Mark II. The arm was designed using decision matrices, static analysis, and inverse kinematics, with validation through simulation in MATLAB, Python, and MuJoCo, along with CAD modeling, additive manufacturing, and custom PCB development. In parallel, the Mark II effort involved defining design requirements, creating conceptual models, and evaluating alternative leg architectures. Simulation results demonstrate that the manipulator arm can reliably reach target positions and perform object interaction tasks, supporting its potential use in automation and interactive demonstrations. Additionally, outreach experiences suggest that the addition of interactive features such as the arm increases engagement and interest among participants. The Mark II design process further identified a ball screw-driven leg mechanism as a promising approach for improving performance and robustness. This work contributes to the continued development of accessible robotics platforms by expanding functionality and strengthening their effectiveness as educational tools, while also laying the groundwork for a more advanced and capable system in future iterations.
Electrical and Computer Engineering, Mechanical Engineering.
Keywords: robotics; engineering; STEM outreach; outreach; quadrupedal robot; robot arm